1993
DOI: 10.1037/0278-7393.19.5.1053
|View full text |Cite
|
Sign up to set email alerts
|

Connecting goals and actions during reading.

Abstract: Three experiments showed that reading about a character's actions can reactivate a goal of the character stated earlier in the passage and backgrounded by intervening material. Subjects were slower to read a line describing an action that was inconsistent with a goal of the protagonist than they were to read about an action that was consistent with the goal, even though both lines were locally coherent. Goals were reactivated even when the intervening material did not describe attempts to achieve the goal (Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
69
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(83 citation statements)
references
References 19 publications
12
69
2
Order By: Relevance
“…In support ofthis idea, when there was an inconsistency with regard to a character's goal (Huitema, Dopkins, Klin, & Myers, 1993), the role of sentence boundaries seemed to have been less critical than in the present experiments. That is, even though well over 50% ofthe target lines (e.g., Then he put on a sweatshirt) did not end with a period, there was an immediate slowdown when they were inconsistent with an earlier stated goal (e.g., George knew he had to cool offor he d get heat stroke).…”
Section: Discussionsupporting
confidence: 49%
“…In support ofthis idea, when there was an inconsistency with regard to a character's goal (Huitema, Dopkins, Klin, & Myers, 1993), the role of sentence boundaries seemed to have been less critical than in the present experiments. That is, even though well over 50% ofthe target lines (e.g., Then he put on a sweatshirt) did not end with a period, there was an immediate slowdown when they were inconsistent with an earlier stated goal (e.g., George knew he had to cool offor he d get heat stroke).…”
Section: Discussionsupporting
confidence: 49%
“…Furthermore, readers holding highimagery sentences in memory showed overall comprehension difficulty in their long reading times of all sentences of the text. The reduction of the contradiction effect to 69 msec for the high-imagery-load participants is quite remarkable, given that this effect, with the same materials, has been both reliable and robust in several published studies (e.g., Albrecht & O'Brien, 1993;Huitema et al, 1993;Myers et al, 1994). One explanation for the loss of the contradiction effect is that for the high-imagery-load participants, holding these sentences required visuospatial resources needed for building a situation model-leading to long reading times and minimal evidence that the text was interpreted.…”
Section: Discussionmentioning
confidence: 96%
“…The critical sentence follows then and states that Mary ordered a hamburger. Using texts such as this, O'Brien and his colleagues (Albrecht & O'Brien, 1993;Huitema, Dopkins, Klin, & Myers, 1993;Myers, O'Brien, Albrecht, & Mason, 1994) have found that reading times for the critical sentence were significantly longer in the inconsistent text condition than in the consistent text condition. This is a situation model effect, because it demonstrates that readers are engaged in maintaining global coherence even when the text is locally coherent.…”
Section: Perceptual Components Of Situation Models Rebecca Fincher-kimentioning
confidence: 99%
“…If they do, reading time for the target sentence should be longer in the inconsistent version than in the consistent one because it is much more difficult, if not impossible, to incorporate the inconsistent information into the integrated situation model. This is exactly what was found for spatial information (e.g., de Vega, 1995;O'Brien & Albrecht, 1992), emotional information (e.g., Gernsbacher, Goldsmith, & Robertson, 1992;Haenggi, Gernsbacher, & Bolliger, 1994), character information (Albrecht & O'Brien, 1993;de Vega, Diaz, & Leon, 1997), and information about the protagonist's goals (Huitema, Dopkins, Klein, & Myers, 1993). Rinck, Hähnel, and Becker (2001) adopted the inconsistency paradigm to examine the representation of temporal information in situation models.…”
mentioning
confidence: 99%